Cross sectional study on exposure to BPA and its analogues and semen parameters in Czech men - Jeseta, Michal; Kalina, Jiri; Franzova, Katerina; Fialkova, Sandra; Hosek, Jan; Mekinova, Lenka; Crha, Igor; Kempisty, Bartosz; Ventruba, Pavel; Navratilova, Jana (Environmental pollution (Barking, Essex, 2024)
Exposure to bisphenols has been found to have adverse effects on male reproductive function in animals. Human exposure to bisphenols is widespread. Bisphenol A (BPA) and its analogues, including bisphenol S (BPS), bisphenol F (BPF), and bisphenol AF (BPAF) are utilized in various consumer products such as food contact materials and dental resins. The effects of these compounds on male fertility and spermatogenesis are unclear and findings from human studies are inconsistent. In this cross-sectional study, we evaluated the influence of BPA, BPS, BPF, BPAF (BPs) measured in semen on number of spermatozoa, total motility, progressive motility, morphology, and DNA fragmentation. We also examined the association of bisphenols (BPs) exposure with patients' occupation. A total of 358 patients aged 17-62 years with BMI 18-42 were included in the study from 2019 to 2021. BPs were extracted using solvent extraction followed by preconcentration step and determined by high-performance liquid chromatography and tandem mass spectrometry (LC/MSMS). Bisphenols were detected in 343 from 349 analysed samples (98.3% of all the samples). In 6 samples, the concentration of all BPs was under the limit of detection and in 20 samples under the limit of quantification. We did not find a statistically significant relationship between occupation and BPs. However, we observed significant correlations between the concentration of BPA and a lower motility and normal morphology. For BPS, a significant correlation with a lower ejaculate volume and a lower total sperm count was found. BPF and BPAF were detected only in 14.3% and 23.9% of samples, respectively. For BPF and BPAF, no significant correlations with spermiogram parameters were observed. Our results show that BPs are widespread in the male population (more than 90% of analysed samples), independently of an occupation and in case of BPA and BPS having a negative impact on spermiogram parameters.
Keywords: Animals; Endocrine disruptors; Semen; průřezové studie; benzhydrylové sloučeniny; Spermatozoa; fenoly; Phenols; lidé; sperma; Fluorocarbons; Cross-Sectional Studies; Benzhydryl Compounds; Male; Bisphenols; Human; Czech Republic; Česká republika; fluorokarbony; mužské pohlaví; zvířata; IVF; Humans